Prove that sec²(90-theta) - 1/( cot²(90- theta) =1
Answers
Answered by
2
Answer:
LHS = sec^2 ( 90 - theta) - 1/(cot^2(90- theta)
we know that
sec^2 (90- theta) = cosec^2
cot^2(90- theta) = tan^2
cosec^2 - 1/ tan^2
1/ sin^2 - 1/ (sin/cos)^2
1/sin^2 - cos^2/sin^2
find LCM between sin^2 and sin^2
LCM between sin^2 and sin^2 is sin^2
1 - cos^2 /sin^2
sin^2/sin^2 = 1
LHS = RHS
Attachments:
![](https://hi-static.z-dn.net/files/d3f/10e300d346f00f6c014acf857a22be5e.jpg)
Answered by
2
Answer:
Answer:
LHS = sec^2 ( 90 - theta) - 1/(cot^2(90- theta)
we know that
sec^2 (90- theta) = cosec^2
cot^2(90- theta) = tan^2
cosec^2 - 1/ tan^2
1/ sin^2 - 1/ (sin/cos)^2
1/sin^2 - cos^2/sin^2
find LCM between sin^2 and sin^2
LCM between sin^2 and sin^2 is sin^2
1 - cos^2 /sin^2
sin^2/sin^2 = 1
LHS = RHS
Similar questions